2007
DOI: 10.1016/j.jfa.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

A nonlocal convection–diffusion equation

Abstract: In this paper we study a nonlocal equation that takes into account convective and diffusive effects,with J radially symmetric and G not necessarily symmetric. First, we prove existence, uniqueness and continuous dependence with respect to the initial condition of solutions. This problem is the nonlocal analogous to the usual local convection-diffusion equation u t = u + b · ∇(f (u)). In fact, we prove that solutions of the nonlocal equation converge to the solution of the usual convection-diffusion equation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 19 publications
1
75
0
1
Order By: Relevance
“…44 However, it can be shown that solutions exist, that the solutions depend continuously on the initial conditions, and that the nonlocal equations converge to the local ones as the nonlocal terms become small enough. [45][46][47][48] Much less information is available about the properties of even linear nonlocal equations in the presence of boundaries, although they are frequently solved numerically. 49 Fortunately, for this particular set of equations, we can make some very compelling arguments indicating that the integral terms are negligible for the purposes of the closure problems.…”
Section: A Localization Of the Closure Problemsmentioning
confidence: 99%
“…44 However, it can be shown that solutions exist, that the solutions depend continuously on the initial conditions, and that the nonlocal equations converge to the local ones as the nonlocal terms become small enough. [45][46][47][48] Much less information is available about the properties of even linear nonlocal equations in the presence of boundaries, although they are frequently solved numerically. 49 Fortunately, for this particular set of equations, we can make some very compelling arguments indicating that the integral terms are negligible for the purposes of the closure problems.…”
Section: A Localization Of the Closure Problemsmentioning
confidence: 99%
“…Here, by the term regularization we mean the modification of the otherwise-zero RHS of the conservation law with terms that are small relative to the scale of the solution. Inspired by the work of Gunzberger and Lehoucq [21] and informed by the work of Ignat and Rossi [25], we propose a regularization of the (inviscid) nonlocal advection equation (2.0.5) of the following form:…”
Section: Regularization Of Non-local Advectionmentioning
confidence: 99%
“…Concerning scalings of the kernel that approximate different problems we refer to [2], [21] and [31], where usual diffusion equations where obtained taking limits similar to the ones considered here.…”
Section: U(0 X) = U 0 (X)mentioning
confidence: 99%